Implementation of project-based learning in English Classroom of Merdeka Curriculum: Student and Teacher Perception - Rambe, Leini Nadira; Suganda, Sonya Puspasari (English Department FBS UNP, 2023)
This research aims to investigate the implementation of project-based learning in English classrooms on two schools selected as “Sekolah Penggerak” who hold Merdeka Curriculum as primary curriculum supervised by government; one is a private school, meanwhile the other one is a public school. Both are the first and pioneer schools who chose to implement the curriculum. Project-based learning is a fundamental approach which underlie the basis of the curriculum; thus, projects are being heavily imposed. This research puts emphasis on project-based learning implementation inside English classroom under newest curriculum in terms of students and teachers’ perception. Mixed-method case study is used; as the instruments such as online questionnaire and interviews are heavily used. The data were collected from 142 participants (140 students and 2 teachers) then were analyzed quantitatively and qualitatively. Findings stated that project-based learning is used based on its own context and characteristics of schools. Students possessed positive views on both the implementation and their teachers implementing project-based learning in English classroom of Merdeka Curriculum. Students are motivated, active and possess critical thinking on their projects. Teachers, in the other side, actively and eagerly to get involved as facilitator to facilitate steps on project-based learning implementation. This research contributes on giving samples and development of project-based learning in English Classroom under newest Merdeka Curriculum.